Association between ethnicity and hypertension in Northern Colombia in 2015 - Drew H. Smith; Jaskaran Grewal; Saba Mehboob; Shiva Mohan; Luisa F. Pombo; Pura Rodriguez; Juan Carlos Gonzalez; Juan Zevallos; Noël C. Barengo (BMC, 2022)
Abstract Background Studies in the United States have shown a genetic predisposition to hypertension in individuals of African descent. However, studies on the associations between ethnic groups and hypertension in Latin America are lacking and the limited results have been inconsistent. The objective of this study is to determine whether Afro-Colombian ethnicity increases the risk of hypertension. Methods This study is a secondary data analysis of a cross sectional study from five provinces in Northern Colombia. Randomly selected individuals (N = 2613; age-range 18-74 years) enrolled in a health care insurance company underwent physical examinations and completed questionnaires regarding ethnicity, lifestyle, and other risk factors. Hypertension in these patients was determined. Unadjusted and adjusted logistic regression analysis were calculated to determine the association between ethnicity and hypertension. Results No association between Afro-Colombian ethnicity and hypertension was found (odds ratio [OR], 0.85; 95% confidence interval [CI], 0.66-1.09). As expected, people with a body mass index (BMI) of 30 or higher were at a greater risk of having hypertension (OR, 3.12; 95% CI, 2.35-4.16) compared with those with a normal BMI. Conclusions Findings from this study suggest no independent association between Afro-Colombian ethnicity and hypertension. Further research should focus on genotyping or socioeconomic factors such as income level.